Adaptation of Space Use during the Covid-19 Pandemic at Costing House Around the Campus Based on Student's Perspective - Vindi Fatma Zahra; Dewi Septanti; Happy Ratna S (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The very rapid growth of Covid-19 has the potential to change the behavior of residents in boarding houses around campus. Especially at the time of the Face-to-Face Meeting (PTM) decision on campus which made most students worried about the condition of their place of residence. Therefore, based on health protocols, students make adaptations for behavior and activities during the pandemic, especially in boarding houses, so there is a need for research to determine the pattern of changes in student behavior in their boarding houses as a result of changes in habits. The purpose of this study was to identify changes in behavior that occurred in student boarding houses due to the Covid-19 pandemic. The objects taken in this study are settlements around the Ten November Institute of Technology (ITS) campus. This study uses the emic paradigm. This study uses content analysis techniques. The use of content analysis techniques is to describe the results of field surveys and interviews that assess changes in behavior, interactions, and activities of boarding house residents. The results obtained are a comparison of learning about behavior, interactions and activities before and after the Covid-19 pandemic.